Population pharmacokinetic analysis and dosing optimization of polymyxin B in critically ill patients - Liang, Danhong; Liang, Zhi; Deng, Guoliang; Cen, Anfen; Luo, Dandan; Zhang, Chen; Ni, Suiqin (Frontiers in Pharmacology, 2023)
Objectives: Since the global broadcast of multidrug-resistant gram-negative bacteria is accelerating, the use of Polymyxin B is sharply increasing, especially in critically ill patients. Unsatisfactory therapeutic effects were obtained because of the abnormal physiological function in patients with intensive care. Therefore, the determination of optimal polymyxin B dosage becomes highly urgent. This study aimed to illustrate the polymyxin B pharmacokinetic (PK) characteristics by defining the influencing factors and optimizing the dosing regimens to achieve clinical effectiveness. Methods: Steady-state concentrations of polymyxin B from twenty-two critically ill patients were detected by a verified liquid chromatography-tandem mass spectrometry approach. The information on age, weight, serum creatinine, albumin levels, and APACHE-II scores was also collected. The population PK parameters were calculated by the nonparametric adaptive grid method in Pmetrics software, and the pharmacokinetics/pharmacodynamics (PK/PD) target attainment rate was determined by the Monte Carlo simulation method. Results: The central clearance and apparent volume of distribution for polymyxin B were lower in critically ill patients (1.24 ± 0.38 L/h and 16.64 ± 12.74 L, respectively). Moreover, albumin (ALB) levels can be used to explain the variability in clearance, and age can be used to describe the variability in the apparent volume of distribution. For maintaining clinical effectiveness and lowering toxicity, 75 mg q12h is the recommended dosing regimen for most patients suffering from severe infections. Conclusions: This study has clearly defined that in critically ill patients, age and ALB levels are potentially important factors for the PK parameters of polymyxin B. Since older critically ill patients tend to have lower ALB levels, so higher polymyxin B dosages are necessary for efficacy.